Influence of aging and maternal protein restriction on PIWI-interacting RNA expression in the offspring rat ventral prostate - Baptista, Hecttor S. [UNESP]; Portela, Luiz M. Frediani [UNESP]; Fioretto, Matheus N. [UNESP]; Mattos, Renato [UNESP]; Ribeiro, Isabelle T. [UNESP]; Lorente, Ana B. Leite [UNESP]; Oliveira, Jordana I. Nascimento; Justulin, Luis A. [UNESP] (Springer Nature, 2024)
The Developmental Origins of Health and Disease (DOHaD) concept explores the link between exposure to adverse conditions during fetal and early childhood development and the onset of chronic non-communicable diseases, such as prostate cancer (PCa). Changes in epigenetics that control gene expression have been identified as potential contributors to the developmental origin of PCa. Piwi-interacting RNAs (piRNAs), for example, control transposable elements (TEs) and maintain genome integrity in germ cells. However, stress-induced deregulation of TEs warrants investigating the role of piRNAs in the prostate gland from the DOHaD perspective, which remains underexplored. This study aimed to detect and characterize piRNA expression in the ventral prostate (VP) of Sprague Dawley rat offspring at 21 postnatal days (PND21) and PND540. The rats were subjected to maternal protein restriction during pregnancy and lactation to understand its impact on prostate development and aging. Histological analyses showed that the gestational and lactation low-protein diet (GLLP) group experienced a delay in prostate gland development, with increased stromal and epithelial compartments and decreased luminal compartments during early life. Aging in this group resulted in decreased luminal compartments and increased stromal areas. Epithelial atrophy was observed in both groups, with an increased incidence of carcinoma in situ in the GLLP group. Small RNA sequencing from control and restricted groups (at PND21 and PND540) identified piRNA clusters in both young and aged animals. We also detected the expression of PIWI genes (Riwi, Rili, Rili2) in the prostate. Our data highlight the key role of maternal malnutrition in modulating piRNA expression in the offspring’s VP, with the potential to influence prostate developmental biology and the risk of prostatic disorders with aging.
Keywords: DOHaD; piRNA; Ventral prostate